Accompanying material for the article 'no value restriction is needed for algebraic effects and handlers' - Pretnar, M (University of Oxford, 2016)
Accompannying material for _No value restriction is needed for algebraic effects and handlers_ ============================================================================================== [Ohad Kammar](http://www.cs.ox.ac.uk/people/ohad.kammar) and [Matija Pretnar](http://matija.pretnar.info/)